The Impact of Diagnostic Feedback to Teachers on Student Learning : Experimental Evidence from India - Muralidharan, Karthik (2012)
We present experimental evidence on the impact of a programme that provided low-stakes diagnostic tests and feedback to teachers, and low-stakes monitoring of classroom processes across a representative set of schools in the Indian state of Andhra Pradesh. We find teachers in treatment schools exerting more effort when observed in the classroom but students in these schools do no better on independently-administered tests than students in schools that did not receive the programme. This suggests that though teachers in the programme schools worked harder while being observed, there was no impact of the feedback and monitoring on student learning outcomes.